Local Wisdom-Based Public Relations Model in Building the Image of the Islamic Communication and Broadcasting Study Program - Akhmad Saoqillah; Azkia Nala; Samsiah Samsiah (STAI Publisistik Thawalib Jakarta, 2025)
The Public Relations strategy in the Islamic Communication and Broadcasting Study Program still relies on conventional approaches, rendering it less contextual and incapable of fostering strong emotional connections with stakeholders. This study aims to analyse a local wisdom-based public relations model implemented to build a positive image of the Islamic Communication and Broadcasting Study Program. The research methodology employs a qualitative approach using a case study method, with data collection techniques including in-depth interviews, participatory observation, and documentation. Data analysis was conducted through thematic analysis and triangulation methods. The results indicate that local wisdom holds significant potential to be integrated into the Public Relations strategy of the Islamic Communication and Broadcasting Study Program at Institut Ummul Quro Bogor to cultivate a positive image relevant to the surrounding community. Currently, the study program has not optimally utilised local cultural elements such as traditional arts, regional languages, and the involvement of community leaders in public communication activities. Digital strategies remain confined to the internal campus environment. This study finds that a local wisdom-based Public Relations model can serve as a strategic approach to enhance public trust, academic appeal, and the cultural identity of the study program. In conclusion, a Public Relations strategy grounded in local wisdom is effective in building image, strengthening community closeness, and supporting the relevance of Islamic communication within both local and global contexts.